DETEKSI MANAJEMEN LABA: PERENCANAAN PAJAK, BEBAN PAJAK TANGGUHAN, ASET PAJAK TANGGUHAN, KEPEMILIKAN MANAJERIAL DAN FREE CASH FLOW (Studi Empiris Perusahaan Manufaktur di Indonesia) - Kartika, Andi; Janah, Afifatul; Hardiyanti, Widhian (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2023)
This study aims to identify profit management in manufacturing companies listed on the Indonesia Stock Exchange based on the factors that influence it, namely: tax planning, deferred tax burden, deferred tax assets, managerial ownership, and free cash flow. Profit management is measured using a profit distribution approach. The sampling method uses purposive sampling with a research period of 2018 to 2020. The relationship and or influence between variables is explained using Multiple Linear Regression Analysis. The results showed that the variables of tax planning, managerial ownership and free cash flow had a positive effect on profit management. Meanwhile, variable deferred tax burdens and deferred tax assets have an insignificant negative effect on profit management.